Connection management for multiwavelength optical networking. - Wei, J.Y (IEEE Journal on selected areas in communications)
This paper describes the connection management research done by the Network Control and Management (NC&M) task force under the multiwavelength optical networking (MONET) program. MONET is sponsored by the Defense Advanced Research Project Agency (DARPA) the US Government Department of Defense, with participation from Bellcore, AT&T, Lucent Technologies, several government agencies, and regional Bell operating companies. MONET's vision is to develop a flexible reliable high-capacity high-performance cost-effective national optical network based on multiwavelength fiber optic technology. As an important component in realizing this vision, the MONET program includes the architecture and design of a prototype network control and management system for MONET's reconfigurable wavelength-division multiplexing (WDM) all-optical network. The primary objectives of the prototype research work are to develop the architecture and framework for managing national-scale transparent reconfigurable WDM optical networks and to demonstrate the feasibility of the NC&M prototype system in a field experiment network in Washington, DC. This prototype system allows the program participants to conduct experiments and gain experience in the management and operations of reconfigurable optical networks. This paper describes the connection management aspects of the prototype system, addressing issues such as the management architecture, information model, and provisioning algorithms of the prototype management system